Bayesian estimation of single and multilevel models with latent variable interactions. Issue 2 (4th March 2021) - Asparouhov, Tihomir; Muthén, Bengt
ABSTRACT: In this article, we discuss single and multilevel SEM models with latent variable interactions. We describe the Bayesian estimation for these models and show through simulation studies that the Bayesian method outperforms other methods such as the maximum-likelihood method. We show that multilevel moderation models can easily be estimated with the Bayesian method.